Data for Siegfried*, Venturelli*, et al., 2023, Geology - Matthew R. Siegfried; Ryan A. Venturelli; Molly O. Patterson; William Arnuk; Timothy D. Campbell; Chloe D. Gustafson; Alexander B. Michaud; Benjamin K. Galton-Fenzi; Mark B. Hausner; Stephanie N. Holzschuh; Bruce Huber; Kenneth D. Mankoff; et al. (Zenodo, 2023)
Datasets used in Siegfried*, Venturelli*, et al. (2023). The life and death of a subglacial lake in West Antarctica, Geology , doi:10.1130/G50995.1. See top-level readme.md file for more information about the types of data and datasets contained in this repository. Code for processing and plotting datasets contained in this repository are contained in our related GitHub repository available at: [https://doi.org/10.5281/zenodo.7605994](https://doi.org/10.5281/zenodo.7605994). This work was supported by the U.S. National Science Foundation (grants 0636970, 0838885, 1327315, 1543347, 1543405, 1543441, 1543537, 1832109, 1832170,and 1836328) and NASA (grants 80NSSC20K1734 and 80NSSC21K0912).